Connexions acadiennes et réseaux marchands français dans l’océan Indien (1762-1785): une marge d’autonomisation? - Vasquez-Parra, Adeline (Acadiensis, 2022)
This article focuses on Acadian social organization after their exile to mainland France from 1762 to 1785. By adopting a unique perspective, margins of empowerment, this article sheds light on various connections established between Acadians and other external agents and social networks in the Indian Ocean from 1762 to 1785. In doing so, the article reveals who these agents were and assesses their impact on Acadian solidarity bonds.